THE ANALYSIS OF RECEPTIONIST SERVICE QUALITY TO INCREASE GUEST SATISFACTION AT BALI RANI HOTEL KUTA - Handayani, Savitri; Bagiastuti, Ni Ketut; Triyuni, Ni Nyoman (Journal of Applied Sciences in Travel and Hospitality; Vol 1 No 2 (2018): June 2018, 2018)
The aim of this study is to analyze receptionist service quality level to increase guest satisfaction at Bali Rani Hotel Kuta. The number of respondent are 60 respondents used accidental sampling for data collect method. Primary data collect of service quality variable used questionnaire method with validity and reliability tested. Analysis technique used SERVQUAL analysis and Importance Performance Analysis applied in Cartesian diagram. The results of this research showed that there are negative, positive and neutral gap between perceptions and guest expectations. Attribute which has negative value gap are number 2, 3, and 4 then attribute which has positive value gap are number 1, 5, 6, 7, 8, 9, 10, 11, 12. Furthermore, based on the Importance Performance Analysis results indicate the position of each attributes in Cartesian diagram, founded the attribute that become a priority to be improved and attributes that become achievements to be maintained. Attribute in quadrant A which is a priority to improved is number 2 about equipment and facilities for support services at the reception are complete. Furthermore, attribute in quadrant B which is the achievements to be maintained are number 1, 4, 7, 11 about the appearance or grooming of the receptionists are neat and clean when serving guests, the hotel information contained in brochures and pamphlets are clear, receptionists able to solve the problem quickly and precisely, security of valuables guests are guaranteed when kept at the reception.